The Effect of International Accounting Standards Implementation, Accountant Training, and Audit Quality on the Reliability of Financial Statements in Public Companies in Indonesia - Loso Judijanto; Ahmad Junaidi (Westscience Press, 2024)
This study examines the impact of International Accounting Standards (IAS) implementation, accountant training, and audit quality on the reliability of financial statements in public companies in Indonesia. A quantitative approach was employed, with data collected from 152 companies using structured questionnaires based on a Likert scale (1–5). Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results indicate that all three independent variables significantly and positively influence financial statement reliability, with audit quality having the strongest impact, followed by IAS implementation and accountant training. Collectively, these factors explain 71.2% of the variance in financial statement reliability, underscoring their importance in improving transparency and accuracy in financial reporting. The findings highlight the need for a holistic approach to enhance financial reporting practices through regulatory compliance, professional training, and high-quality audits.